2020
DOI: 10.1371/journal.pntd.0008809
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microtranscriptome profiles reveal distinct expression of microRNAs in severe leptospirosis

Abstract: Biomarkers to predict the severity of leptospirosis are still lacking. This study aimed to identify and validate microRNAs in patients with severe leptospirosis, that could potentially be used as biomarkers for predicting an unfavorable outcome. Serum samples were collected from participants with definite diagnosis of leptospirosis. The participants were divided into two groups, non-severe and severe leptospirosis, as defined by the Specific Organ Sequential Organ Failure (SOFA) Score of more than two in any o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Moreover, a previous study identified specific miRNAs that were able to discriminate the infection from other acute febrile diseases with a high sensitivity and specificity [ 21 ]. Additionally, our group recently demonstrated distinct expression of circulating microRNAs as novel biomarkers for identifying severe leptospirosis [ 22 ]. However, there is very limited information regarding the expression of circulating miRNAs in patients with leptospirosis in the context of liver-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study identified specific miRNAs that were able to discriminate the infection from other acute febrile diseases with a high sensitivity and specificity [ 21 ]. Additionally, our group recently demonstrated distinct expression of circulating microRNAs as novel biomarkers for identifying severe leptospirosis [ 22 ]. However, there is very limited information regarding the expression of circulating miRNAs in patients with leptospirosis in the context of liver-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial injury markers already observed in leptospirosis‐associated AKI are the intercellular adhesion molecule‐1 (ICAM‐1) and syndecan‐1 22 . The difference in microtranscriptome profiles, including serum miR155‐5p and miR630, was shown as a possible biomarker for patients with severe versus non‐severe leptospirosis 36 . Diagnostic tests recommended by World Health Organization (WHO) including microscopic agglutination test (MAT), direct culture and polymerase chain reaction technique require advanced facilities which are not universally available 37 .…”
Section: Tropical Infectionmentioning
confidence: 98%
“…22 The difference in microtranscriptome profiles, including serum miR155-5p and miR630, was shown as a possible biomarker for patients with severe versus non-severe leptospirosis. 36 Diagnostic tests recommended by World Health Organization (WHO) F I G U R E 1 Pathogenesis of leptospirosis-associated AKI and factors associated with severity of leptospirosis-associated AKI. Leptospira migrate to the renal tubulointerstitium.…”
Section: Leptospirosismentioning
confidence: 99%